(untitled) (Revista Contexto & Educação, 2026)
This study aims to analyze the understandings of early childhood education teachers regarding psychomotor practices and their connection to pedagogical work in the teaching and learning processes of five-year-old children. The research was based on the premises of a qualitative approach and was conducted through a case study. Data were generated through a literature review, participant observation, narrative interviews, and document analysis. Data analysis was based on the Nuclei of Meaning proposed by Aguiar and Ozella (2006; 2013). The findings revealed that teachers understand psychomotor practices and their connection to pedagogical work through playful experiences, highlighting, in this relationship, the children’s bodily, social, and cognitive realms. However, it was found that, in the dialogue with pedagogical work, Psychomotricity is not intentionally included, signaling gaps in relation to the initial or continuing training of teachers with regard to knowledge about the aforementioned Science.